Post-cognitive psychology - Jonathan Potter (2000)
This paper speculates about what will, and should, follow cognitivism in psychology in the new century. It highlights the importance of the work of Wittgenstein, Sacks and Edwards for the development of post-cognitive psychology. Cognitivism is criticized for failing to conceptualize practices in a way that recognizes their action orientation and co-construction, and to appreciate how they are given sense through people's categories, formulations and orientations. Discursive psychology focuses on the production of versions of reality and cognition as parts of practices in natural settings. It is offered as one potential successor to cognitivism.